Western Political Thought in Dialogue with Asia - Nederman, Cary J.; Shogimen, Takashi (Lexington Books, 2008)
Given the rise of globalization and coinciding increase in cultural clashes among diverse nations, it has become eminently clear to scholars of political thought that there exists a critical gap in the knowledge of non-Western philosophies and how Western thought has been influenced by them. This gap has led to a severely diminished capacity of both state and nonstate actors to communicate effectively on a global scale. The political theorists, area scholars, and intellectual historians gathered here by Takashi Shogimen and Cary J. Nederman examine the exchange of political ideas between Europe and Asia from the Middle Ages to the early twentieth century. They establish the need for comparative political thought, showing that in order to fully grasp the origins and achievements of the West, historians of political thought must incorporate Asian political discourse and ideas into their understanding. By engaging in comparative studies, this volume proves the necessity of a cross-disciplinary approach in guiding the study of the global history of political thought.